Oral presentation Monitoring mosquito population (Diptera Culicidae) in Cyprus - Vasquez Christodoulou, Marlen (My University, 2026)
Violaris M, Vasquez MI, Andreou M, Hadjivassilis, A, Wirth MC, Monitoring mosquito population (Diptera Culicidae) in Cyprus, Oral presentation, 12th Pan-hellenic Entomological Conference, Larnaka, Cyprus, 13-16 November 2007.